Revealing Chronic Granulomatous Disease in a Patient With Williams-Beuren Syndrome Using Whole Exome Sequencing - Ripen, Adiratna Mat; Chiow, Mei Yee; Rama Rao, Prakash Rao; Mohamad, Saharuddin Bin (Frontiers in Immunology, 2021)
Blended phenotypes exhibited by a patient may present a challenge to the establishment of diagnosis. In this study, we report a seven-year-old Murut girl with unusual features of Williams-Beuren syndrome (WBS), including recurrent infections and skin abscesses. Considering the possibility of a second genetic disorder, a mutation screening for genes associated with inborn errors of immunity (IEI) was conducted using whole exome sequencing (WES). Analysis of copy number variations (CNVs) from the exome data revealed a 1.53Mb hemizygous deletion on chromosome 7q11.23, corresponding to the known WBS. We also identified a biallelic loss of NCF1, which indicated autosomal recessive chronic granulomatous disease (CGD). Dihydrorhodamine (DHR) flow cytometric assay demonstrated abnormally low neutrophil oxidative burst activity. Coamplification of NCF1 and its pseudogenes identified a GT-deletion (∆GT) at the start of exon 2 in NCF1 (NM_000265.7: c.75_76delGT: p.Tyr26Hisfs*26). Estimation of NCF1-to-NCF1 pseudogenes ratio using ∆GT and 20-bp gene scans affirmed nil copies of NCF1 in the patient. While the father had a normal ratio of 2:4, the mother had a ratio of 1:5, implicating the carrier of ∆GT-containing NCF1. Discovery of a 7q11.23 deletion involving one NCF1 allele and a ∆GT in the second NCF1 allele explained the coexistence of WBS and CGD in our patient. This study highlights the capability of WES to establish a molecular diagnosis for a case with blended phenotypes, enabling the provision of appropriate prophylactic treatment.